Computer modelling of energy turnover and body temperatures in elite cyclists during climbing: steep, steeper, Angliru; cold, colder, Gavia - van Beek, J. H. G. M. (Journal of Science and Cycling, 2015)
Climbing very steep mountain roads (e.g. Monte Zoncolan, Angliru) or high passes with sub- zero temperatures at the summit (e.g. Gavia, Stelvio) imposes intense stress on the physiological system during professional bicycle races. Previously we simulated energy conversion and heat transfer in the human body during bicycle racing with computer models [1]. In this presentation climbs are simulated on increasingly steeper slopes to investigate how the body copes with the large heat generation. Ascents and descents at low temperatures are also simulated, suggesting that unexpected temperature profiles may emerge in the body.